Historical Reflections Building Castles in the Air. - Ensmenger, Nathan (Communications of the ACM, 2011)
The author reflects on the history of computer programmer recruiting and training in the mid-20th century when computer technology started to emerge. Basic skills needed to be hired as a computer programmer in those times are said to have included an orderly mind and a lively imagination. Advertisements posted by the International Business Machines (IBM) Corporation are discussed.